The relevance of finance within a sustainable business model in vulnerable populations - Reátegui Vela, Walther Hernán (2021)
Objective: Analyze the relevance of the finance within a sustainable business model in vulnerable population. Method: A qualitative research was carried out, based on the review of the applicable literature including the concepts of sustainability, sustainable finance, value chains, climate change and circular economy. Also, it included the review of bibliographic databases such as Scopus, Clarivate, Academia, and Google Scholar. The literature review of classical finance was excluded. Results: It has been identified that financial aspects are included in the management of sustainable business; however, these are carried out in a conventional way, making it difficult for them to reach the necessary funds. A model is proposed, which is approached from a value chain perspective and considers the management of environmental, social and economic risks, seeking that those who face the most risk receive the highest return. Conclusion: In order to achieve that a conceptual model is implanted, in which sustainable finance has a clear participation, it is relevant to ensure greater empowerment to the populations that are being favored through better financial training; likewise, it is essential that the financing sources deepen their evaluation concerning risks and returns, and that the results are measurable in the financial statements of each business.